Genome-wide identification of TCP transcription factors and their potential roles in hydrolyzable tannin production in Quercus variabilis cupule - Yaochen Wang; Yaochen Wang; Yaochen Wang; Jinjin Li; Jinjin Li; Jinjin Li; Yixin Chen; Yixin Chen; Yixin Chen; Zhaowei Yu; Zhaowei Yu; Zhaowei Yu; et al. (Frontiers in Plant Science, 2024)
Hydrolyzable tannins (HTs) have garnered significant attention due to their proven beneficial effects in the clinical treatment of various diseases. The cupule of Chinese cork oak (Quercus variabilis Blume) has been used as raw material of traditional medicine for centuries for its high content of HTs. Previous studies have identified UGT84A13 as a key enzyme in the HT biosynthesis pathway in Q. variabilis, but the transcriptional regulation network of UGT84A13 remains obscure. Here, we performed a comprehensive genome-wide identification of the TCP transcription factors in Q. variabilis, elucidating their molecular evolution and gene structure. Gene expression analysis showed that TCP3 from the CIN subfamily and TCP6 from the PCF subfamily were co-expressed with UGT84A13 in cupule. Further functional characterization using dual-luciferase assays confirmed that TCP3, rather than TCP6, played a role in the transcriptional regulation of UGT84A13, thus promoting HT biosynthesis in the cupule of Q. variabilis. Our work identified TCP family members in Q. variabilis for the first time, and provided novel insights into the transcriptional regulatory network of UGT84A13 and HT biosynthesis in Q. variabilis, explaining the reason why the cupule enriches HTs that could be used for traditional medicine.